Strategi Peningkatan Mutu Pelayanan Rumah Sakit Melalui Akreditasi - Mutiyatul Muslimah (CV. SINAR HOWUHOWU, 2026)
Hospital service quality is an important indicator in assessing the success of healthcare service delivery. As public expectations for safe, effective, and patient-centered healthcare continue to increase, hospitals are required to implement various continuous quality improvement strategies. One of the most widely adopted strategies is hospital accreditation, which serves as a mechanism for quality evaluation and improvement through the implementation of service standards, patient safety measures, organizational governance, and risk management. This study aimed to review strategies for improving hospital service quality through accreditation based on published research findings. The study employed a literature review approach by examining scientific articles retrieved from Google Scholar, PubMed, ScienceDirect, SpringerLink, Scopus, and Garuda databases. The reviewed articles were published between 2014 and 2026 and met the predetermined inclusion and exclusion criteria. The findings indicate that accreditation contributes positively to improving hospital service quality, particularly in patient safety, compliance with standard operating procedures, improvement of clinical documentation, strengthening organizational governance, and fostering a sustainable quality culture. The success of accreditation implementation is influenced by management commitment, human resource competency, organizational support, resource availability, and consistency in applying accreditation standards. Although several challenges remain in its implementation, accreditation has proven to be an effective strategic instrument for supporting continuous quality improvement in hospitals. Therefore, hospitals should integrate accreditation into their organizational culture to achieve high-quality healthcare services and patient safety.